Effects of Low-Cost Airlines on Domestic Tourism Economy in Thailand - LAW, Colin C.H.; PROMPITAK, Kamontorn; WONGWATTANAKIT, Chatchawan (Journal of Environmental Management and Tourism, 2022)
Air deregulation in 2003 led to the development of the low-cost airline industry in Thailand. The new airlines entered the air transport industry market and helped to further increase tourism destinations across the country, motivating more internal travel. This study aims to examine the impact of low-cost airlines factors on tourism demand and to identify the relationship between low-cost airlines and domestic tourism in Thailand. ARDL (Autoregressive Distributed Lag) model was applied to analyse the long-run and short-run relationship between the dependent variables and domestic tourism demand. The findings show that the chosen economic variables in this study are showing importance in determining the number of domestic tourists particularly in the long-run but a less significant relationship in the short run. The increasing connectivity between the cities, especially between the rural and metropolitan areas is stimulating travel and trade.